„Knobology“ in Doppler ultrasound - Loewe, Axel; Jenssen, Christian; Hüske, Sebastian; Zander, David Y.; Ignee, André; Lim, Adrian; Cui, Xin-Wu; Dong, Yi; Hoffmann, Beatrice; Dietrich, Christoph F. (Medical ultrasonography, 2021)
Ultrasonography is a ubiquitous and indispensable diagnostic and therapeutic tool in medicine. Due to modern equipment and automatic image optimization, nowadays the introduction of ultrasound imaging requires only little technical and physical knowledge. However, profound knowledge of the device function repertoire and underlying mechanisms are essential foroptimal image adjustment and documentation. From a medical as well as an aesthetic point of view, the goal should always be to achieve the best possible image quality. This article provides an overview of handling of ultrasound systems, fundamental adjustments and their optimization in Doppler ultrasound.
Gesehen am 11.10.2022